Telephone Headset Sound Exposure Assessment by Threshold Comparison - Miyara, Federico (2011)
There is concern about the occupational sound exposure of people working at call centers. There are two standard methods to measure sound immission from headsets. The first one, known as microphone in real ear (MIRE) uses a tiny microphone or probe inside the ear canal. The second uses an artificial ear or head with microphones at the bottom of the artificial canals. Both methods require expensive equipment, which is not easy to justify for an occupational health service. We propose a method using only readily available equipment. It consists in three steps. First, the headset is electrically calibrated by comparing the hearing threshold (which is assumed to be independent of the source) with the headset under test and with standard audiometric earphones. Second, the electric signal received by the telephone headset during normal use is digitally recorded. Finally, the recorded signal is converted into its acoustic equivalent taking into account any equalisation needed to compensate for the known response of the audiometric earphones and the already measured response of the headset. This method has been implemented by software running on a portable computer and HDA 200 audiometric earphones.